The Rig - Ducie, Joe (Houghton Mifflin Harcourt, 2015)
"Fifteen-year-old Will Drake has made a career of breaking out from high-security prisons. His talents have landed him at the Rig, a specialist juvenile holding facility in the middle of the Arctic Ocean. No one can escape from the Rig. No one except for Drake"--